1991
DOI: 10.1007/bf01649287
|View full text |Cite
|
Sign up to set email alerts
|

Vermindertes Plasmacarnitin bei Typ-I Diabetes mellitus

Abstract: Realizing the importance of carnitine for the lipid and carbohydrate metabolism and the possible role for glucose utilization and myocardial function carnitine concentrations in type I and type II diabetic patients in plasma, erythrocytes and 24 h urine were determined. The plasma levels of carnitine were significantly diminished in type I diabetic patients compared to controls, while carnitine concentrations in erythrocytes and 24 h urine did not differ from controls. Plasma carnitine levels did not change si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
7
1
6
Order By: Relevance
“…Because CPT1 and CrAT share similar carnitine binding motifs ( 31 ), these data support the notion that carnitine acyltransferases are susceptible to inhibition when local carnitine concentrations fall. This observation is particularly relevant to obesity, diabetes, and other disease conditions associated with carnitine insuffi ciency ( 2,(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, results from the current study suggest that the mitochondrial pool of free carnitine is more prone to depletion than other compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Because CPT1 and CrAT share similar carnitine binding motifs ( 31 ), these data support the notion that carnitine acyltransferases are susceptible to inhibition when local carnitine concentrations fall. This observation is particularly relevant to obesity, diabetes, and other disease conditions associated with carnitine insuffi ciency ( 2,(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, results from the current study suggest that the mitochondrial pool of free carnitine is more prone to depletion than other compartments.…”
Section: Discussionmentioning
confidence: 99%
“…This leads of course to a decrease of free carnitine concentrations in the patients. This mechanism, probably responsible for the observed higher concentration of LCA in urine, was described for acylcarnitines in plasma and tissue [21]. Compared to the controls, the free carnitine concentration of insulin-treated diabetics is in the same range with an average of 18 µg mL -1 .…”
Section: Acylcarnitine Pattern Of Diabetes Mellitus Patientsmentioning
confidence: 74%
“…It was suggested that L-carnitine was lost by urine [60]. Also, it has been proposed that it is convenient to treat diabetic patients with L-carnitine [61,62].…”
Section: Inhibition Of Apoptosis and Necrosis With Acetyl-l-carnitinementioning
confidence: 99%
“…A number of studies demonstrated that cytokines could be modulated with the addition of acetyl-L-carnitine and L-carnitine [62]. We investigated if L-carnitine could modify the "in vitro" inhibition of insulin release of normal ß-cells when they were co-cultured with splenocytes from diabetic mice [81].…”
Section: Studies Supporting the Proposed Treatmentmentioning
confidence: 99%
See 1 more Smart Citation